Aplikasi Microsoft Expresion Web Pada Guru Mata Pelajaran IPS SMP Negeri 1 Kendari - Junaidin; Nongko, Pahenra (Amaliah: Jurnal Pengabdian Masyarakat, 2017)
State Junior High School (SMP Negeri) 1 Kendari is an international standard school and became a favorite school as well as a pilot school. With the teachers of social studies subject as the target of HPM UMK program, the application of Microsoft expression web on a social science studies teacher at SMP Neg. 1 Kendari is truly helpful. This application contains learning draft, including the title, objectives, materials, and evaluation and became field as the impact of the development of information technology. The purpose of this program is the creation of mediabased learning Microsoft web expression on the teachers of SMP Neg.1 Kendari, especially social studies, so that this web-based method can increase students’ motivation in achieving the lesson. In addition, it allows teachers to deliver teaching materials easily and to enrich the knowledge of teachers who have been using LCD media conventionally. The method used is the method of development of Research and Development (R&D) through three stages; preliminary studies, model development stages and the evaluation stage. The result in this program is that a learning program of Microsoft expression application has improved the ability of 5 social studies teachers in using and applying learning media by using Microsoft expression web application. The partner was excited and enthusiastic in practicing the media which has been taught. Web-based media used as a reference in the development of instructional media and increase insight to the social studies teachers and students in making web-based learning media in SMP Neg. 1 Kendari.